Internalization of religious moderation in Banjarharjo Village, Karanganyar - Galih Fajar Fadillah; Andry Nur Haryanto; Farah Nilawati; Ernawati Ernawati; Anni Nurul Hidayati; Ahmad Nafi’; Uswatun Marhamah (Community Empowerment, 2023)
Banjarharjo Village is a village that is suitable for instilling the value of moderation, especially religious moderation. But in reality tolerance from a religious perspective is still lacking. This community service aims to internalize moderation in society, especially religious education. The method used is PAR, with the stages of planning, implementing, observing and reflecting. The results of the activity showed a positive response from the TPQ manager, village residents and village officials, that how important it is as religious people living in a plural society to uphold the philosophy of moderation in religion.